Factors Affecting the Value of Ankle Brachial Index in Patients with Diabetes Mellitus Type 2: Literature Review - Sri Bintari Rahayu Rahayu; Takdir Tahir Tahir; Kadek Ayu Erika Erika (STIKep PPNI Jawa Barat, 2022)
Aims: The purpose of this literature review is to determine the factors that affect the value of the Ankle Brachial Index (ABI) in patients with type 2 diabetes mellitus. Methods: Search articles through Pubmed, Science Direct, Scopus and Researchgate. The articles obtained were filtered based on full text, 20 articles were found, and six articles were analyzed through analysis of objectives, suitability of topics, research methods used, characteristics of respondents, and the results of each article, published 2017-2021, in English and Indonesian. Results: ABI value in people with diabetes is influenced by age with a lower prevalence of ABI higher in men, treatment with oral anti-diabetic or insulin, mean arterial pressure, the severity of diabetic foot, and the presence of symptoms of complications of diabetes mellitus such as diabetic retinopathy. However, the duration of suffering from diabetes mellitus did not affect the abnormal ABI value. Conclusion: The Ankle Brachial Index (ABI) value can be influenced by Age, Gender, the severity of diabetic foot, and symptoms of complications, but the length of suffering from Diabetes Mellitus does not affect the ABI value.